Mapping of the Coronavirus Membrane Protein Domains Involved in Interaction with the Spike Protein - de Haan, Cornelis A. M. (American Society for Microbiology, 1999)
The coronavirus membrane (M) protein is the key player in virion assembly. One of its functions is to mediate the incorporation of the spikes into the viral envelope. Heterotypic interactions between M and the spike (S) protein can be demonstrated by coimmunoprecipitation and by immunofluorescence colocalization, after coexpression of their genes in eukaryotic cells. Using these assays in a mutagenetic approach, we have mapped the domains in the M protein that are involved in complex formation between M and S. It appeared that the 25-residue luminally exposed amino-terminal domain of the M protein is not important for M-S interaction. A 15-residue deletion, the insertion of a His tag, and replacement of the ectodomain by that of another coronavirus M protein did not affect the ability of the M protein to associate with the S protein. However, complex formation was sensitive to changes in the transmembrane domains of this triple-spanning protein. Deletion of either the first two or the last two transmembrane domains, known not to affect the topology of the protein, led to a considerable decrease in complex formation, but association was not completely abrogated. Various effects of changes in the part of the M protein that is located at the cytoplasmic face of the membrane were observed. Deletions of the extreme carboxy-terminal tail appeared not to interfere with M-S complex formation. However, deletions in the amphipathic domain severely affected M-S interaction. Interestingly, changes in the amino-terminal and extreme carboxy-terminal domains of M, which did not disrupt the interaction with S, are known to be fatal to the ability of the protein to engage in virus particle formation (C. A. M. de Haan, L. Kuo, P. S. Masters, H. Vennema, and P. J. M. Rottier, J. Virol. 72:6838–6850, 1998). Apparently, the structural requirements of the M protein for virus particle assembly differ from the requirements for the formation of M-S complexes.